The developmental lipidome of Nippostrongylus brasiliensis - Tao Wang; Michael G. Leeming; Nicholas A. Williamson; Tiffany Bouchery; Rory Doolan; Graham Le Gros; Gavin E. Reid; Nicola L. Harris; Robin B. Gasser (Parasites & Vectors)
Abstract Background Nippostrongylus brasiliensis—a nematode of rodents—is commonly used as a model to study the immunobiology of parasitic nematodes. It is a member of the Strongylida—a large order of socioeconomically important parasitic nematodes of animals. Lipids are known to play essential roles in nematode biology, influencing cellular membranes, energy storage and/or signalling. Methods The present investigation provides a comprehensive, untargeted lipidomic analysis of four developmental stages/sexes (i.e. egg, L3, adult female and adult male stages) of N. brasiliensis utilising liquid chromatography coupled to mass spectrometry. Results We identified 464 lipid species representing 18 lipid classes and revealed distinct stage-specific changes in lipid composition throughout nematode development. Triacylglycerols (TGs) dominated the lipid profile in the egg stage, suggesting a key role for them in energy storage at this early developmental stage. As N. brasiliensis develops, there was a conspicuous transition toward membrane-associated lipids, including glycerophospholipids (e.g. PE and PC) and ether-linked lipids, particularly in adult stages, indicating a shift toward host adaptation and membrane stabilisation. Conclusions We provide a comprehensive insight into the lipid composition and abundance of key free-living and parasitic stages of N. brasiliensis. This study provides lipidomic resources to underpin the detailed exploration of lipid biology in this model parasitic nematode. Graphical Abstract